Ischemic Necrosis of the Gastric Remnant Treated Successfully Using Total Remnant Gastrectomy - Tetsuhiro Hara; Noriaki Tokumoto; Kensuke Shimbara; Tomohiro Adachi; Hideaki Hanaki; Manabu Shimomura; Yoshiro Aoki; Mikihiro Kano; Toshihiko Kohashi; Jun Hihara; Mahito Funakoshi; Mayumi Kaneko; et al. (Case Reports in Gastroenterology, 2022)
Distal gastrectomy (DG) with lymph node dissection is considered as the standard treatment for gastric cancer. Ischemic necrosis of the gastric remnant is a rare but serious complication of DG that requires careful consideration for early diagnosis and treatment to lower the associated mortality rate. A 71-year-old male presented to our hospital with hyperglycemia and was evaluated for suspected diabetes. The patient’s medical history was otherwise unremarkable. Computed tomography (CT) revealed a thickening of the stomach wall, with follow-up esophagogastroduodenoscopy revealing type 3 gastric cancer in the greater curvature of the antrum. Biopsy specimen confirmed a pathological diagnosis of mucinous adenocarcinoma, with a clinical diagnosis of cT3N0M0, cStageIIB. An open DG with Billroth I reconstruction was performed, without incident. On postoperative day 1, the patient developed a high fever, abdominal pain, and elevated white blood cell count (12,200/μL). On postoperative day 2, his C-reactive protein level increased to >30 mg/dL. CT revealed an edematous thickening of the stomach wall, with poor mucosal enhancement of the remnant stomach and thinning of the anastomosis wall, with air nearby. Emergency surgery was performed for suspected leakage. Intraoperative findings showed no evidence of leakage. Intraoperative endoscopy revealed a necrotic gastric remnant, and we performed a total remnant gastrectomy with Roux-en Y reconstruction. The patient was discharged in a stable condition, 25 days after the first surgery. Although ischemic necrosis of the gastric remnant is a rare complication, its possibility should be carefully considered after DG, for early diagnosis and treatment.